CHALLENGES AND OPPORTUNITIES IN TEACHER PROFESSIONAL DEVELOPMENT: A CASE STUDY OF POST-FUNDAMENTAL SCHOOLS IN BUJUMBURA PROVINCE, BURUNDI - Elvis, Manariyo; Srivastava, Sujata (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study examines the challenges and opportunities in teacher professional development in post-fundamental schools in Bujumbura Province, Burundi. A sample of 92 teachers from 15 randomly selected post-fundamental schools participated in the study. Data were collected using a 32-item questionnaire, covering aspects such as the need for professional development, programme organisation, resource availability, and participation. The findings revealed significant challenges, including inadequate organisation of programmes, insufficient time allocation, a lack of infrastructure, and disparities in participation. Despite these challenges, there is a strong demand for professional development among teachers, with particular needs identified in areas such as ICT and pedagogy. The study highlights key opportunities to improve professional development by better organising programmes, increasing teacher involvement in decision-making, and providing adequate resources and incentives. Addressing these issues could significantly enhance the quality of education in post-fundamental schools in Bujumbura Province.